Possible protection against drug-induced hepatotoxicity by certain natural agents - Wessam Hamdy Abdelaziz Elessawy; Ezz Eddeenp Abdelazez Eldenshary; Somaia Ahmed Nada (Cairo : Wessam Hamdy Abdelaziz Elessawy, 2013)
The aim of the current study was evaluate the protective effect of ALA, L-carnitine, ginseng and CoQb10 (Bagainst isoniazid induced hepatotoxicity in rats . Thirty six male Sprague-Dawley (SD) rats were allocated into different groups and over a 3-week period they were treated intraoperitoneally ({u2160}.P) either with INH alone (100mg/kg b.w)s
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacology and Toxicology
Issued also as CD
Keywords: Hepatotoxicity; Isoniazid; L- carnitine